Herbivorous fish rise as a destructive fishing practice falls in an Indonesian marine national park. Issue 8 (9th September 2019) - Bejarano, Sonia; Pardede, Shinta; Campbell, Stuart J.; Hoey, Andrew S.; Ferse, Sebastian C. A.
Abstract: Securing ecosystem functions is challenging, yet common priority in conservation efforts. While marine parks aim to meet this challenge by regulating fishing through zoning plans, their effectiveness hinges on compliance levels and may respond to changes in fishing practices. Here we use a speciose assemblage of nominally herbivorous reef fish in Karimunjawa National Park (zoned since 1989) to investigate whether areas subject to a restrictive management regime sustained higher biomass over seven years compared to areas where moderate and permissive regulations apply. Using a trait‐based approach we characterize the functional space of the entire species pool and ask whether changes in biomass translate into changes in functional structure. We track changes in predator biomass, benthic community structure, and fishing practices that could influence herbivore trajectories. Overall herbivore biomass doubled in 2012 compared to 2006–2009 and remained high in 2013 across all management regimes. We found no evidence that this biomass build‐up resulted from predator depletion or increased food availability but suggest it emerged in response to a park‐wide cessation of fishing with large drive nets known as muroami. The biomass increase was accompanied by a modest increase in taxonomic richness and a slight decrease in community‐scale rarity that did not alter functional redundancy levels. Subtle changes in both functional specialization and identity of assemblages emerged as generalist species with low intrinsic vulnerability to fishing recovered sooner than more vulnerable specialists. While this implies a recovery of mechanisms responsible for the grazing of algal turfs and detritus, restoring other facets of herbivory (e.g., macroalgal consumption) may require more time. An increase in the cost‐benefit ratio per journey of muroami fishing facilitated a ban on muroami nets that met minimal resistance. Similar windows of opportunity may emerge elsewhere in which gear‐based regulations can supplement zoning plans, especially when compliance is low. This does not advocate for implementing such regulations once a fishery has become unprofitable. Rather, it underlines their importance for breaking the cycle of resource depletion and low compliance to zoning, thus alleviating the resulting threats to food security and ecosystem integrity.